A contribuição técnica e artística do processo de mixagem de áudio utilizando Ambisonics. - José Ricardo Barboza (2017)
The present Master's dissertation focuses on the process of musical production in three-dimensional spatialisation environments using Ambisonics techniques.Through the analysis of concepts and methodologies of traditional musical production, the observation of the musical content produced using the Ambisonics techniques and the research on the Ambisonics techniques and the technologies derived from it, it is intended to produce musical content in a system of spatialization. From this production process, it is planned to collect a set of good practices that could qualify the same.